The practice of complementary feeding among stunted children under the age of two - Inne Soesanti; Pinky Saptandari; Sri Adiningsih; M. Bagus Qomaruddin (MDPI AG, 2020)
Stunting is caused by chronic malnutrition and recurrent infectious diseases. Stunting in Pasongsongan Village affects less than 20% of the children under two, leading to problems in growth in early childhood. Ocean fish is the main animal products in this village on the coast, but it turned out that it is not served to the children, even if they should have begun to be introduced to animal products by the age of 9 months. The purpose of this study was to observe the practices of complementary feeding among stunted children under the age of two in Pasongsongan Village. This research was carried out by qualitative method. The informants were twelve mothers of children under the age of two. Data was collected from interviews, observations and documentation. The stunted children only consumed rice porridge until the age of one, which means that the food intake contains mostly carbohydrates. The mothers who have stunted children have argued that the children's intestines is not strong enough to digest food with coarser texture like eggs, fish, beef and chicken. Sea fish are given when the children can walk because there has long been a belief that fish contain worms. No feeding fishes and other animal products that are good source of protein can affect their growth in a nega- tive way. The feeding practice of stunted children under the age of two in Pasongsongan Village was strongly influenced by culture. The mindsets of mothers of the stunted children regarding feeding practices must be changed.